INHIBITING THE HOUSE CROW (Corvus splendens) DAM AGE ON MAIZE GROWTH STAGES WITH REFLECTING RIBBONS IN A FARMLAND - N. Akram; H. A. Khan; M. Javed (Journal of Animal and Plant Sciences, 2013)
Present paper provides information on minimizing the damage caused by the house crow (Corvus splendens L) on the developmental stages (dough and mature) of maize in an irrigated cropland using the reflecting ribbons. Of all observations per three arbitrarily divided three field stations. For the unprotected conditions, highest damage 15.36±0.74 occurred towards the left hand side, and the lowest, 3.97±0.24 was recorded in the middle of the field. In the ribbon protected conditions, both highest and lowest damages were 1.43 and 0.73, for the left hand side and middle of the crop, thereby, considerably reducing the crow depredations. Present studies also augment that, use of reflecting ribbons and allied non chemical repellents, would not only diminish damage from a variety of birds on economically important crops, but also prevent economic losses, to maintain ecological stability and sustainability in the productive agro-ecosystems of Pakistan.
Keywords: house crow; maize; damage; repellents; management